Apparent Argatroban Resistance in a Patient with Elevated Factor VIII Levels. (July 2013) - Kennedy, Dina M; Alaniz, Cesar
OBJECTIVE: To report a case in which there was a lack of activated partial thromboplastin time (aPTT) correlation with plasma argatroban concentrations in a patient with elevated factor VIII levels who was diagnosed with heparin-induced thrombocytopenia (HIT). CASE SUMMARY: A 59-year-old female with a history significant for basal cell carcinoma was transferred from an outside hospital and underwent resection of a third ventricle mass. The postoperative hospital course was complicated by subdural hematoma, HIT, and pulmonary embolism. Upon initiation of argatroban, we faced difficulty in maintaining therapeutic aPTT values despite administration of significantly higher than usual doses of argatroban (up to 7 μg/kg/min). A coagulation abnormality was suspected and an argatroban concentration was obtained; results showed an elevated level of 2.2 μg/mL (therapeutic range 0.4–1.2), with a corresponding aPTT of 53.1 seconds. A coagulopathy workup revealed an excess of factor VIII activity. Thereafter, argatroban concentrations were used for dose adjustments and the infusion was titrated to a final rate of 2.75 μg/kg/min. DISCUSSION: The lack of correlation of aPPT values with argatroban administration has not been described in the literature and, to our knowledge, similar cases have not been reported. We were unable to achieve an increase in aPTT, despite aggressive argatroban dosing in a patient with increased factor VIII activity. A definitive mechanism for this is not entirely known; however, it is thought to be secondary to contributing underlying causes such as excessive clotting factors, circulating inflammatory proteins, or other aspects. CONCLUSIONS: With the initiation of argatroban therapy, particular attention should be given to ensure that aPTTs correlate with dosing to prevent life-threatening bleeding complications. Excessive argatroban dosing requirements should prompt further investigation into potential confounders such as elevated factor VIII levels.